A low-power consumption MZI thermal optical switch with a graphene-assisted heating layer and air trench. Issue 63 (16th August 2017) - Sun, Yue; Cao, Yue; Yi, Yunji; Tian, Liang; Zheng, Yao; Zheng, Jie; Wang, Fei; Zhang, Daming
Abstract : Low-power consumption MZI thermal optical switches with graphene-assisted heating layers and air trenches have been designed and simulated. Abstract : To reduce the power consumption of thermal optical switches, graphene-assisted hybrid MZI structures were designed and simulated. The hybrid waveguide structures were composed of polymer cores, silica lower claddings, air trenches, and graphene-assisted heating layers. Because of the high thermal-optic coefficient of the polymer, excellent thermal conductivities of silica and graphene, and the air trench structures, the power consumption of the hybrid structures could be reduced to below 0.95 mW. The graphene-assisted heating layers were also designed to bury the waveguide cores or to contact the surface of the waveguide cores for more efficiently conducting the heat of electrodes to the waveguide cores. Moreover, the side heating electrodes introduced were found to be compatible with the designed graphene-assisted heating layers. The polarization and the absorption of both rectangle and ridge waveguide structures were analyzed through optical field simulation. Based on the optimized parameters, the thermal fields were simulated, and the heating efficiencies of the graphene-assisted hybrid structures could be increased by 78% as compared to those of the top electrode device without a graphene layer. Our simulation comprises two MZI thermal optical switches with an optimized balance between the switching power consumption and the switching time. One MZI thermal optical switch with a lower power consumption realized the switching power consumptions of only 0.39 mW and the switching times of 30 μs and 92.4 μs, whereas the other switch with faster switching times achieved the switching power consumptions of 0.95 mW and the switching times as fast as 1 μs and 81.6 μs.